Rate and Proportion Analysis of The Decision Model from Online Learning Sustainability - Sihotang, Erna Fransisca Angela; Alam, Islam Nur (Jurnal Informatika, 2023)
The human development index is built by three fundamental dimensions: long life and healthy life, knowledge, and a decent standard of living. This research was inspired by sustainable development goal four, Quality Education. Quality of education has an excellent relation with knowledge management. The fuzzy logic-based decision support model of online course learning suggests nine parameters to be considered. This research collaborates those nine parameters, participation rate, and the Proportion of youth and adult involvement in formal and non-formal education. The result shows that from the participation rate, it concluded that those with stable expansion also consistently enrich their knowledge by attending formal or non-formal learning; female constantly takes learning more than male; people who lived in city has more urge to learn than people who live in villages. From the Proportion from 2017, 2018 and 2022, people with ICT skills increased significantly, showing good value. Nevertheless, while female participation in learning is higher than male, it does not make female has better skills than male. Last, needed an innovation to gain interest in study to village residents.